2019
DOI: 10.1002/jcb.28524
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐503 contributes to podocyte injury via targeting E2F3 in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is serious diabetic complication with capillary injury. Podocyte injury exerts a crucial effect on DN pathogenesis. MicroRNA-503 (miR-503) has been reported in various diseases including DN. Here, we investigated the detailed mechanism of miR-503 in the podocyte injury of DN. The functional role of miR-503 was investigated in cultured podocytes and diabetic rats. Podocyte injury was evaluated by migration and apoptosis experiments in podocytes and we observed that high glucose elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
4
19
0
1
Order By: Relevance
“…1B ). Among these aberrantly expressed miRNAs, miR-146a, miR-214 and miR-503 were increased, which was consistent with previous reports ( 6 , 20 , 21 ), indicating the reliability of the present microarray. Of the downregulated miRNAs, miR-199a-3p was identified as one of the most significantly downregulated.…”
Section: Resultssupporting
confidence: 93%
“…1B ). Among these aberrantly expressed miRNAs, miR-146a, miR-214 and miR-503 were increased, which was consistent with previous reports ( 6 , 20 , 21 ), indicating the reliability of the present microarray. Of the downregulated miRNAs, miR-199a-3p was identified as one of the most significantly downregulated.…”
Section: Resultssupporting
confidence: 93%
“…In terms of apoptosis and cell death, miR-503 expression was higher in DN mice, and it negatively inhibits the expression of E2F transcription factor 3 (E2f3), and E2f3 is the transcription factor that is involved in the regulation of cell apoptosis, differentiation, and development (Zha et al, 2019). Reduction of the E2f3 expression leads to podocyte cells apoptosis and injury, induced by high glucose (Zha et al, 2019).…”
Section: Micrornas In Autophagy and Apoptosismentioning
confidence: 99%
“…In terms of apoptosis and cell death, miR-503 expression was higher in DN mice, and it negatively inhibits the expression of E2F transcription factor 3 (E2f3), and E2f3 is the transcription factor that is involved in the regulation of cell apoptosis, differentiation, and development (Zha et al, 2019). Reduction of the E2f3 expression leads to podocyte cells apoptosis and injury, induced by high glucose (Zha et al, 2019). Importantly, in the mice model of DN treated with Losartan (a drug for kidney disease treatment), the prevention of DN progression in those mice was evident with the inhibition of miR-503 action (Zhu et al, 2016), therefore confirming the role of miR-503 in contributing to podocyte cell death.…”
Section: Micrornas In Autophagy and Apoptosismentioning
confidence: 99%
“…A study has shown that E2F3 plays a key role in muscle and bone development and affects the normal growth of mice [34]. Inhibition of E2F3 expression promotes the development of diabetic nephropathy [35]. Furthermore, E2F3 plays a key role in various biological processes such as lens development, cardiac neovascularization, DNA damage response, and neuronal migration [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%